A Representação da Mulher na Câmara dos Deputados: trajetória, atuação política e reeleição das parlamentares gaúchas no período de 2007 a 2011 - Fonseca, Isabel Cristina de Carvalho (2012)
This dissertation aims at analyzing the representation of women in the Chamber of Deputies, specifically gaucho women parliamentarians in the period between 2007 and 2011. The purpose of this study is to investigate the trajectory, mandate and campaign for reelection of the women who made up the female caucus of Rio Grande do Sul, in the 53th Legislature of the Federal Chamber . The performance of these representatives is investigated from different moments of participation in the political: who walked in the path of building their political careers at the time of representation (in the legislative arena) and in the pursuit of votes to remain in office (electoral arena).This analysis gives birth to concepts of political representation, recognition and political capital. Moreover, brings discussions about the underrepresentation of women in politics brazilian institutional and a brief account of the history of the feminist movement in Brazil. It also analyzes the theories about feminist politics and inclusion of women in political parties in Brazil. The data for empirical research were taken mainly from the electronic addresses of the Federal Chamber, the Superior Electoral Court and representatives of blogs. It was concluded that the presence of women in federal parliament gaucho, more specifically the Chamber of Deputies, has been important in the brazilian institutional policy. His work and ideas gradually gain strength and prominence, showing the relevance of a relationship between the presence of political and policy ideas. The participation of these women in various committees of the Chamber of De puties and the range of propositions of his own in different thematic areas, visibility beyond that achieved during their careers and in proportional elections of 2010, can contribute effectively so that more women will achieve political power since as the y gain more prominence and visibility, increase political capital and demonstra te the potential of woman to conquer spaces historically relegated only to males